VLSI Design Of A Bit Serial Arithmetic Logic Unit - Lee, Tiong Kiat (2003)
The arithmetic logic unit (ALU) is designed to perform bit serial operation on two 8 bits input. In this project , a Very High Speed Integrated Circuit Hardware Description Language (VHDL) code is written using the Altera MAX+Plus II environment to design, compile and simulate for each operation in the bit serial arithmetic logic unit. The details of each design steps from design entry, compilation, debugging, simulation and syntheis is described in this project.